Validation of the name Osbeckia tirunelvelica (Melastomataceae) - Kottaimuthu, Ramalingam; Gnanasekaran, Gunadayalan (Phytotaxa, 2015)
During the taxonomic revision of the genus Osbeckia Linnaeus (1753: 345) from the Western Ghats, India, we came across few interesting specimens from the Manjolai hills in Kalakkad Mundanthurai Tiger Reserve (KMTR), Tirunelveli, Tamil Nadu. Critical studies with relevant literature revealed the identity of the collected specimens as Osbeckia tirunelvelica Manickam & Murugan (2001: 626). Unfortunately the name Osbeckia tirunelvelica was not validly published by Manickam & Murugan (2001), because, contrary to Art. 40 of ICN (McNeill et al. 2012), two collections were indicated as “type”. Therefore, the name Osbeckia tirunelvelica is validated here by indicating a single collection as the holotype.